2019
DOI: 10.1248/cpb.c19-00511
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot on the Current Status of Alzheimer’s Disease, Treatment Perspectives, <i>in-Vitro</i> and <i>in-Vivo</i> Research Studies and Future Opportunities

Abstract: Alzheimer's Disease (AD) is one of the most challenging diseases faced by humankind. AD is still not classified as curable because of the complex structure of pathologies underlying it. As the mean life expectancy of the world population constantly increases, the prevalence of AD and treatment costs for AD also grow rapidly. Current state of the art for AD treatment mainly consists of palliative therapy aimed at providing symptomatic relief and improving the standard of living in patients with AD. However, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 185 publications
0
4
0
Order By: Relevance
“…This disease often leads to memory loss, cognitive impairment, difficulties in daily tasks, and behavioral problems in patients . With the aging of the global population and the steady increase in average life expectancy, the incidence of AD also correspondingly increased . AD has gradually become an increasingly serious health problem, with significant impacts on individuals and society .…”
Section: Introductionmentioning
confidence: 99%
“…This disease often leads to memory loss, cognitive impairment, difficulties in daily tasks, and behavioral problems in patients . With the aging of the global population and the steady increase in average life expectancy, the incidence of AD also correspondingly increased . AD has gradually become an increasingly serious health problem, with significant impacts on individuals and society .…”
Section: Introductionmentioning
confidence: 99%
“…About 50 million people worldwide suffer from AD, and the number is increasing year by year. It is estimated that the number of AD patients will exceed 115 million by 2050 . However, the single-target drugs such as galanthamine and memantine used in the clinical treatment of AD can only improve a certain link of AD, with problems such as different curative effects and great toxic and side effects, which cannot improve or even reverse the course of the disease .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the number of AD patients will exceed 115 million by 2050. 1 However, the single-target drugs such as galanthamine and memantine used in the clinical treatment of AD can only improve a certain link of AD, with problems such as different curative effects and great toxic and side effects, which cannot improve or even reverse the course of the disease. 2 Currently, there are no specific drugs for AD, and the development of highly effective anti-AD drugs with few side effects has become a hot research topic.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD), an age-related neurodegenerative disease, has become the most common dementia and accounted for almost 60%–80% of all cases 1 . The epidemiological data indicated that the prevalence of AD is increasing with the world's population ageing.…”
Section: Introductionmentioning
confidence: 99%